Immobilization of silver nanoparticles at varying concentrations on segments of polyvinyl chloride manufactured endotracheal tubes (2024)
ABSTRACT: Ventilator-associated pneumonia (VAP) remains a significant challenge in intensive care units, representing a primary medical device-associated infection with alarming incidence rates. Patients undergoing mechanical ventilation are particularly vulnerable to VAP due to bacterial accumulation on the endotracheal tube cuff, which can lead to biofilm formation and subsequent migration into the lower respiratory tract, resulting in pneumonia. Currently, various strategies are being explored to mitigate VAP incidence. These approaches encompass innovations in endotracheal tube design, tracheal secretion aspiration systems, material surface modifications, and others. However, a fully effective solution to prevent biofilm formation has not yet been developed. Despite ongoing efforts to address VAP through innovations in endotracheal tube design and other preventive measures, a comprehensive solution to effectively prevent biofilm formation has remained elusive. In this study, we have researched the potential of surface modification processes to mitigate bacterial colonization on endotracheal tubes manufactured from polyvinyl chloride (PVC). Specifically, we explored the introduction of silver nanoparticles (AgNPs) at varying concentrations as a strategy to prevent bacterial adherence and biofilm formation. We successfully validated the chemical modification of the surface and subsequent nanoparticle immobilization. This result was accomplished by scrutinizing physicochemical alterations through wetting studies, Fourier Transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). Through examination of physicochemical alterations using Fourier-transform infrared spectroscopy (FTIR), wetting studies, and scanning electron microscopy (SEM), we successfully validated the efficacy of the surface modification process proposed and confirmed the immobilization of AgNPs. We conducted mechanical strength assays, revealing that the surface modification process with silver nanoparticles did not compromise the mechanical integrity of the material. Additionally, we conducted antimicrobial efficacy and in vitro cytotoxicity assessments of the modified endotracheal tubes. Our findings indicate that the material modified with a 100 % concentration of silver nanoparticles exhibited promising results in reducing bacterial colonization, particularly against Klebsiella pneumoniae and Pseudomonas aeruginosa strains. It is worth mentioning that we observed no cytotoxic effects on L929 cells, underscoring the safety profile of the modified material for potential clinical application. In conclusion, our study highlights the potential of surface modification with silver nanoparticles as a promising strategy to mitigate bacterial colonization on endotracheal tubes and reduce the risk of VAP in mechanically ventilated patients. These findings contribute to ongoing efforts to enhance patient safety and improve outcomes in critical care settings. Further research and clinical trials are warranted to validate the effectiveness and long term benefits of this innovative approach in preventing VAP and minimizing associated morbidity and mortality